Earthworms from Mato Grosso, Brazil, and new records of species from the state - Bartz, Marie Luise Carolina; Pasini, Amarildo; Brown, George Gardner (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to undertake a qualitative assessment of earthworm diversity in areas under human influence, in a region of Cerrado–Pantanal–Amazon rainforest transition, in the state of Mato Grosso, Brazil. The earthworms were collected in the municipalities of Barra do Bugres and Arenápolis, and were studied together with species previously identified from other municipalities. Seventeen municipalities, at 29 sampling points of Mato Grosso State, have been sampled. Seven species of earthworms were collected and identified in Barra do Bugres: Goiascolex vanzolinii, Pontoscolex (Pontoscolex) corethrurus, Opisthodrillus borellii borellii, Opisthodrillus sp., Dichogaster (Diplothecodrilus) gracilis, Dichogaster sp. and a species of the Criodrilidae family. Four species of earthworms were identified in Arenápolis: Pontoscolex (Pontoscolex) corethrurus, Dichogaster (Diplothecodrilus) gracilis, Dichogaster (Diplothecodrilus) affinis and Dichogaster sp. In total, 32 earthworm species/subspecies are known from Mato Grosso, 22 native and 10 exotic.